Molecular cytogenetics reveals an uncommon structural and numerical chromosomal heteromorphism in Zephyranthes brachyandra (Amaryllidaceae) - Nascimento, Tiago (2022)
Background and aims: Zephyranthes brachyandra belongs to a tribe of ornamental Amaryllidaceae native of South America, whose genera circumscription and phylogenetic relationships are still unclear. Cytologically, Z. brachyandra is a tetraploid whose chromosomes are of similar size and morphology, hindering the identification of its 2n = 24 chromosomes. The aim of this study was to investigate the stability of the many CMA+ and DAPI+ bands and the occurrence of B chromosomes by a cytomolecular approach.M&M: For this investigation we conducted a cytomolecular analysis with CMA/DAPI staining and fluorescence in situ hybridization with 5S and 35S rDNA probes, and the TTTAGGG telomeric probe.Results: In the present work, a cytomolecular analysis of Z. brachyandra, revealed a large and variable number of CMA+ and DAPI+ heterochromatic bands and 5S and 35S rDNA sites, and a regular distribution of the TTTAGGG telomeric sequences. In addition, one individual was monotrisomic with 2n = 24, and another one had a B chromosome. Both numerical and structural chromosome alterations were clearly characterized by CMA/DAPI bands and rDNA sites.Conclusions: Comparing the present data with the cytological data for other species of Zephyranthes, it becomes clear that a cytomolecular approach is fundamental to the understanding of the chromosome variation and cytotaxonomy of the group.